Antibacterial Activity of Kecombrang Flower Extract Toward Pathogenic and Food Spoilage Bacteria - Rifda Naufalin; Betty Sri Laksmi Jenie; Feri Kusnandar; Mirnawati Sudarwamto; Herastuti Rukmini (Jurnal Teknologi dan Industri Pangan, 2005)
In this study, kecombrang flowers was extracted with non polar (hexane), semipolar (ethil acetate) and polar (ethanol) solvent. The result revealed that ethil acetat and ethanol extracts inhibited 7 bacteria, i.e : spore forming bacteria (Bacillus cereus), Gram positive bacteria (Staphylococcus aureus) and (Listeria monocytogenes), Gram negative bacteria (Salmonella typhimurium, Aeromonas hydrophila and Escherichia coli), spoilage bacteria (Pseudomonas aeruginosa) but did not inhibit Lactobacillus plantarum. The hexane extract did not show antimicrobial activity. On well diffusion test, ethil acetate developed clear zones of 12.3 – 27.3 mm (diameters) and this was higher than ethanol extract 11.0-15.4 mm (diameters). The MIC (minimum inhibitory concentration) of ethil acetate and ethanol extract against the seven bacteria were 3-13 mg/ml. Key words : Kecombrang (Nicolia speciosa), antibacteria, extract